OPTIMALISASI LAYANAN KONSELING INDIVIDU BAGI SISWA DENGAN MASALAH KELUARGA DI SMA NEGERI 1 SIAU TIMUR - Tamalonggehe, Nadajasia Rosseto; Pontoh, Chanesa Angelica; Susmantoyo, Rhea S.N. (PT. Giat Konseling Nusantara, 2025)
Family problems are one of the factors that have a significant impact on the psychological and academic development of students at school. At SMA Negeri 1 Siau Timur, a number of students experience obstacles in the learning process and self-adjustment due to unfavorable family situations. Some of them come from broken home families, while others live in intact families but experience a lack of attention and affection due to unbalanced parenting patterns such as having to give in to younger siblings, being burdened with domestic responsibilities, or losing emotional figures from busy parents. This situation affects emotional stability, learning concentration, and even student academic achievement. Individual counseling services, as one of the approaches in Guidance and Counseling at school, have a strategic role in helping students overcome these internal problems. This article aims to explore how individual counseling services can be optimized in accompanying students who are facing family problems, as well as compiling contextual and empathetic intervention strategies to support students’ psychological well-being and academic achievement. The approach used involves case observations, analysis of student needs, and the development of counseling service strategies that are integrative and based on human relationships.